Defect-enabled fast gas hydrate kinetics for energy and decarbonisation applications - Ngoc N. Nguyen; Mirza Galib; Anh V. Nguyen; Praveen Linga (Journal of CO2 Utilization)
Gas hydrates are gas-carrying water structures with proven relevance to the sustainability future. Nature showcases these gas-carrying water structures through multi-trillion tones of methane encapsulated in natural gas hydrates (NGHs) on Earth. Experimentations successfully produced gas hydrates containing ∼5 wt% of hydrogen, 15 wt% of methane or 30 wt% of CO2. These water-based gas carriers hold great promise for efficient energy storage and CO2 sequestration. However, unlocking this potential has been impossible due to slow gas hydrate kinetics. Here, we propose a conceptually new approach, termed defect engineering, for rationally introducing structural defects into gas hydrate structures (using polar dopants) and creating defect-enabled gas mobility for enhanced gas hydrate kinetics. This approach is supported by preliminary experiments. While the supporting evidence remains incomplete, our discussions are grounded in a foundational basis and open up a new avenue of research in gas hydrates toward sustainable applications, especially, harnessing the CO2 (waste)/CH4 (energy) exchange in NGHs for simultaneously achieving energy recovery and carbon-neutrality.